2022
DOI: 10.1088/1361-665x/ac6ea2
|View full text |Cite
|
Sign up to set email alerts
|

Developments on auxetic closed cell foam pressure vessel fabrications

Abstract: Auxetic foam can have higher indentation resistance, better protection under impact and higher vibration damping than conventional foam. Unlike auxetic open cell foam, with established, commercially viable options for manufacturing, methods for making auxetic closed cell foam are not established. We revisited pressure-vessel methods, proposed in 1996, for making auxetic closed cell foam. We processed low-density polyethylene foam for six hours at 400 to 700 kPa and 100 °C, causing foams to shrink by a factor o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 72 publications
2
15
0
Order By: Relevance
“…[ 32 ] But this trend has been reported several times in the literature for NPR foams. [ 7,8,21,22,30–32 ] Figure 6 also shows that NPR can be observed up to 65% of deformation. Unfortunately, no data about PS auxetic foams have been reported in the literature to compare.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…[ 32 ] But this trend has been reported several times in the literature for NPR foams. [ 7,8,21,22,30–32 ] Figure 6 also shows that NPR can be observed up to 65% of deformation. Unfortunately, no data about PS auxetic foams have been reported in the literature to compare.…”
Section: Resultsmentioning
confidence: 89%
“…Duncan et al reported on the preparation of auxetic foams via steam (water vapor) treatment, [ 21 ] and a pressure‐vessel method (vacuum). [ 22 ] The original foam was sheets of closed‐cell LDPE foam with a density of 60 kg/m 3 . Poisson's ratios as low as −0.3 in tension and −1.1 in compression were obtained, while only −0.2 was obtained for the vacuum method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical metamaterials [1,2,3,4,5,6,7,8,9,10,11,12,13] are rationally-designed structures capable of exhibiting a plethora of atypical mechanical properties that are rarely observed in the case of naturally-occurring materials. Some of the most commonly studied of such properties are negative Poisson's ratio [14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29] (auxetic behaviour), negative stiffness [30,31,32,33,34] and negative compressibility [35,36]. Over the last thirty years, it has been demonstrated that devices utilising materials exhibiting such characteristics can be used in the case of a variety of applications including protective devices [37,38], sports equipment [39] as well as biomedical [40,41] and vibration damping devices [42,43,44].…”
Section: Introductionmentioning
confidence: 99%
“…[28] Auxetic foams are mainly found in form of opencell configurations, although techniques to transform closed-cell foams by steam and pressure do also exist. [29][30][31] The most established manufacturing process to produce auxetic open-cell foams consists of a volumetric compression, annealing via heating, cooling, and relaxation. [32][33][34][35] Volumetric compression creates the typical re-entrant cell structures of auxetic materials, while heating and cooling provide the thermoforming of the compressed foam, so that the shape of the re-entrant cell structures stabilizes after the foam is released from compression.…”
mentioning
confidence: 99%